The influence of the addition of date palm fibers on the thermo-mechanical proprieties of the earth bricks. - Hachem CHAIB; Abdelouahed KRIKER (Universty of El-oued جامعة الوادي, 2019)
Algeria is located in an area with a high solar potentiality, and presents nearly 90 % of arid and semi-arid lands, of this fact it is important to look at the current situation of Saharan cities. The objective in the context of this work is the achievement of a level of thermal comfort with a lower energy consumption and a mechanical resistance acceptable with a reduced cost. For this, we have tried to make bricks with good thermal characteristics and mechanical basis of three local materials: namely the clay of Baldet Amer the sand dune of Sidi Khouiled and fibers of date palm.
Intervention
Keywords: —Saharan Regions; Thermal properties; Mechanical properties; Sand Dune; Clay; Brick